Evaluative and Reflective Study of Translation Learning Design: An Instructional Analysis - Maria Botifar; Asti Ramadhani Endah Lestari; Eka Apriani (AL-ISHLAH: Jurnal Pendidikan, 2023)
This article aims to describe the result of the instructional analysis of the learning design of Translation I and II courses used at one of the public universities in Jambi. Using the Dick and Carey’s model, this research focuses on two steps analysis: goal analysis and subordinate skills analysis. The data used was the syllabus of Translation 1 and Translation II courses which have been used previously. However, there is a crucial need to evaluate the quality of the learning design to improve the students’ learning outcomes. The results of the analysis showed that 1) the learning objectives need to be described in detail regarding the competencies students will achieve. 2) There is no description of competencies that lead to translation skills, so the portion of learning that emphasizes cognitive aspects is more than psychomotor and affective aspects. 3) Learning materials put more emphasis on the process rather than the products. 4) It does not describe practical translation approaches, methods and strategies but rather the translation process, such as translation history or translation difficulties. 5) Evaluation of translation learning needs to be described in detail because it only focuses on knowledge/cognitive aspects rather than the translation learning process.